Experimental simulation of fracture initiation and morphology in tight sandstone gas reservoirs temporary plugging fracturing - KONG Xiangwei,XU Hongxing,SHI Xian,CHEN Hang (Youqicang pingjia yu kaifa)
This study addresses the challenges presented by the reservoirs in He-8 member in SD block of Ordos Basin, characterized by low porosity, low permeability, strong heterogeneity, and conventional fracturing fracture shapes. Utilizing fracture mechanics, this research examines the interactions between temporarily blocked fractures and the initial fracture throughout their entire contact period. Key considerations include fluid pressure drop within the fracture and the rock mechanics parameters of the reservoirs in He-8 member. The study systematically analyzes the influence of various parameters such as fracture strike, well deviation angle, and azimuth angle on fracturing fracture parameters. Notable findings include: Fracturing pressure decreases with increasing well deviation angle and azimuth angle. The initiation angle diminishes as well inclination increases, reaching a nadir before decreasing further with azimuth angle adjustments. Using artificial cement samples and a large-scale experimental system with realistic triaxial physical models, the study simulates the initiation, turning, and propagation behaviors of new fractures in temporary plugging fracturing. The behaviors of initiation, steering and extension of newly formed fractures at different well inclination and azimuth angles were evaluated along with the parameters such as fracture initiation pressure and fracture stimulated area. The experimental results reveal: Both initial and secondary fracture pressures tend to decrease as well inclination increases, making fractures more prone to turning and significantly enlarging the modifiable area. With consistent trap inclination, fracture initiation pressure decreases and the fracture modification area expands as bore azimuth increases. Fractures resulting from azimuthal 90° spiral perforation exhibit greater complexity compared to those from azimuthal 0° spiral perforation. Additionally, fixed surface perforation techniques can regulate fracture pressure and the initial fracture positions in horizontal wells, recommending a perforation angle between 75° and 90°. These findings offer valuable insights for the design of temporary plugs and fracturing strategies in low-permeability tight sandstone oil and gas reservoirs.